Vulneración del principio de celeridad procesal en los procesos de autorización de viaje de menor - Shinno Pereyra , Vanessa Elizabeth (2023)
The present work focuses its objectives on carrying out an analysis of the minor travel authorization procedures for the 2019 period to verify if there is indeed a violation of the principle of procedural speed in non-litigious procedures where the authorization is processed in case of dissent from one of the parents, as stated in article 112 of the Children and Adolescents Code.